The Buckingham Catastrophe in multiscale modelling of fracture. (12th July 2011) - Chen, James; Lee, James D.
Two original/modified Ball-Grimes models and one original/modified Lewis-Catlow models, are used in multiscale modelling of mixed mode fracture of Magnesia. The specimen is decomposed into a far field (modelled by linear elastic fracture mechanics), a near field (modelled by Atomistic Field Theory) and a crack-tip region (modelled by molecular dynamics). When two atoms get too close during the simulation of crack propagation, the attraction force artificially overcomes the repulsive barrier (Buckingham Catastrophe). The numerical results of three original models show significantly different phenomena. To demonstrate the sensitivity of interatomic potential and to prevent the catastrophe, three modified models are used. Numerical results of three modified models are compared and discussed.